Symptoms Associated With Personal Protective Equipment Among Frontline Health Care Professionals During the COVID-19 Pandemic - Çağlar, Ahmet; Kaçer, İlker; Hacımustafaoğlu, Muhammet; Öztürk, Berkant; Öztürk, Kemal (Disaster medicine and public health preparedness, 2022)
Personal protective equipment (PPE) use is frequently construed as inconvenient and disturbing by health care professionals (HCPs). We hypothesized that new-onset symptoms among HCPs may be associated with extended use of PPE and aimed to investigate risk factors related with new-onset symptoms. In addition, the effects of new-onset symptoms on working performance were evaluated. In this cross-sectional study, 315 participants filled out a questionnaire that contains 4 main parts: (1) demographics, (2) new-onset symptoms with PPE use, (3) PPE usage hours, and (4) personal opinion about the effect of sensed symptoms on working performance. The mean age was 31.58 ± 4.6 years, and 50.5% (n = 159) were female. New-onset symptom rate was 66% (n = 208). The most common new-onset symptom was headache (n = 115, 36.5%) followed by breathing difficulty-palpitation (n = 79, 25.1%), and dermatitis (n = 64, 20.3%). Extended use of PPE, smoking, and overweight were independently associated with developing new-onset symptoms. A clear majority of symptomatic participants pointed out the impact on working performance (193/208, 92.7%). Hospitals should take the necessary precautions (eg, shorter shifts and more frequent breaks) to prevent symptoms associated with PPE and ensure that HCPs comply with these precautions.